Balancing Societal Needs and Regulatory Certainty: The Case Study of Peramivir in Japan. Issue 4 (15th January 2013) - Tominaga, T; Ando, Y; Nagai, N; Sato, J; Kondo, T
<x xml:space="preserve">Abstract</x> Regulators must balance societal and medical requirements against the need for certainty about benefit and risk for new medicines. This is described in a case study of the expedited review and approval of peramivir, a novel neuraminidase inhibitor, in Japan in the context of the emergence of new strain of influenza in 2009. The case illustrates the importance of regulatory science and transparency in supporting such decision making. Clinical Pharmacology & Therapeutics (2013); 93 4, 342–344. doi:10.1038/clpt.2012.268